Gender differences in the effects of psychological interventions on multidimensional state anxiety prior to competition in Malaysian volleyball players / Dr. Lim Boon Hooi & Balbir Singh Gill - Lim, Boon Hooi; Gill, Balbir Singh (Faculty of Sports Science and Recreation, 2011)
The purpose of this study was to investigate gender differences in the effects of psychological interventions on multidimensional state anxiety prior to competition in Malaysian volleyball players. The Competitive Sport Anxiety Inventory – Revised (CSAI-2R) was employed to examine the pre-competition multidimensional state anxiety one day before competition at the competition venue. Subjects were youth state volleyball players (N=96; boys = 48; girls = 48; Age: M= 16.35 yr., SD = .89 yr) competing in the under 18 National School Sport Council of Malaysia Volleyball Tournament. The group with the highest group mean scores in cognitive state anxiety was assigned to a cognitive intervention group (n=24; 12 boys & 12 girls) where subjects underwent breathing techniques and autogenic relaxation with music lasting 30 minutes per session; the group with the highest group mean scores in somatic anxiety component (n=24; 12 boys & 12 girls) completed the somatic intervention with progressive muscular relaxation lasting 30 minutes; the self-confidence group (n=24; 12 boys & 12 girls) which rated the lowest mean group scores in self- confidence component carried out the intervention with positive self-talk and goal setting exercises lasting 30 minutes; and a control group (n=24; 12 boys & 12 girls). The MANOVA indicated that the interaction effect for gender and type of intervention on CSAI-2R components was significant (Wilks’s Lambda = .69, F (7, 88) = 3.73, p < .001). The results indicated significant main effect for gender (Wilks’s Lambda = .79, F (7, 88) = 7.57, p < .001) and type of intervention (Wilks’s Lambda = .13, F (7, 88) = 30.85, p < .001). The male athletes in the present study displayed lower somatic state anxiety, lower cognitive state anxiety and higher self-confidence intensities than female athletes one day prior to competition, gender did influence anxiety responses and findings of this study partially supported the hypothesis.